2020
DOI: 10.1111/jace.17501
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and enhanced adsorption properties for CO2 and dyes of amino‐decorated hierarchical porous BCN aerogels

Abstract: Anthropogenic CO 2 emission has an enormous increase in recent decades, which is the most momentous input to the greenhouse effect and leads to a range of environmental concerns such as global warming, sea level rising, desertification, and so on. 1,2 Therefore, CO 2 capture is considered as a great challenge. In addition, nowadays different kinds of dyes are extensively used in numerous fields of up-to-date technology, including textiles, cosmetics, leather, food, paper production, photo electrochemical cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Their isotherms can be classified as type IV, suggesting the shell of the hollow spheres with mesopores. 48 , 49 According to the pore size distribution curve of the two samples (inset in Figure 6 b), it is shown that they have uniform pore size distribution mainly in the range of 2.5–10 nm, which is consistent with the results in Figure 3 . The BET surface area of the double-shelled hollow sphere (509 m 2 /g) is larger than those of the single-shelled hollow spheres (333 m 2 /g), indicating that the presence of two shells in the former contributes to the increase of BET surface areas.…”
Section: Resultssupporting
confidence: 86%
“…Their isotherms can be classified as type IV, suggesting the shell of the hollow spheres with mesopores. 48 , 49 According to the pore size distribution curve of the two samples (inset in Figure 6 b), it is shown that they have uniform pore size distribution mainly in the range of 2.5–10 nm, which is consistent with the results in Figure 3 . The BET surface area of the double-shelled hollow sphere (509 m 2 /g) is larger than those of the single-shelled hollow spheres (333 m 2 /g), indicating that the presence of two shells in the former contributes to the increase of BET surface areas.…”
Section: Resultssupporting
confidence: 86%
“…where q e (mg g −1 ) is the equilibrium adsorption amount, Q 0 (mg g −1 ) is the maximum adsorption amount, b (L mg −1 ) is a constant term related to the energy of adsorption, C e (mg L −1 ) is the equilibrium concentration of dye in the solution, k F and n are the Freundlich constants, k F represents the adsorption capacity of the adsorbent, and n indicates how favorable the adsorption process is (n=2∼10, 1∼2, and <1 indicate good, moderate, and poor adsorption, respectively) [59] …”
Section: Methodsmentioning
confidence: 99%
“…where q e (mg g À 1 ) is the equilibrium adsorption amount, Q 0 (mg g À 1 ) is the maximum adsorption amount, b (L mg À 1 ) is a constant term related to the energy of adsorption, C e (mg L À 1 ) is the equilibrium concentration of dye in the solution, k F and n are the Freundlich constants, k F represents the adsorption capacity of the adsorbent, and n indicates how favorable the adsorption process is (n = 2 ~10, 1 ~2, and < 1 indicate good, moderate, and poor adsorption, respectively). [59] Photocatalytic activity: The photocatalytic activity was evaluated by carrying out the photodegradation of the MB dye under whitelight irradiation (Bridge lux BXRA-50 C5300; λ > 410 nm). In a typical experiment, MB (20 mL, 10 mg L À 1 ) and the prepared material (20 mg) were mixed in a glass vial in the dark and under continuous stirring until an adsorption-desorption equilibrium was reached.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…The amine-modified hierarchical porous BCN aerogels showed superior adsorption of organic dyes and CO 2 . The carbon doping and amino functionalities in chemically functionalized BCN synergistically improved the adsorption activities and accelerated the dye adsorption kinetics . The structural and electronic changes in h -BN because of C and O doping weakened the B–N linkages and enhanced the electronic polarity.…”
Section: Introductionmentioning
confidence: 99%